Failure handling in the primary crushing sector of a mining company: a contribution to maintenance management (Research, Society and Development, 2021)
The main goal of this work was to perform analysis and treatment of failures in the primary crushing sector, and verify their contributions to the maintenance management of the Planning and Crushing sector of a mining company. The analysis indicated that the highest number of corrective incidents occurred in a primary gyratory crusher, which consisted of obstruction in the feed by blocks of rock (boulders). This obstruction was caused by deformation of the concave plates and excessive clearance in regions of the crushing chamber. The plates on the opposite side of the boulders’ displacement had a length of 1201.3 ±2.0 mm, while the plates in the displacement region had 1221.0 ±8.0 mm length. Based on this difference, follow-up and inspection were carried out during a period of four months, through observation and by failure indicators analysis. The analyzes indicated that during the crusher's feeding process, the material with the highest granulometry reached only one side of the crushing chamber, the A side, causing greater compression effort in this region, due to the impacts of the boulders. In order to mitigate this issue, a new resin, with greater compression strength, was recommended, which was developed and applied to the intermediate plates of the concaves. After applying the new resin and performing further analysis of the failure indicator, it was noted that the deformation and clearance events of the crusher concave plates were reduced by approximately 66.7%. This result contributed to greater availability of the equipment and increased productivity in the company's primary crushing sector.